Introducing dental local anaesthesia using a standardized cognitive behavioural technique - Vestjord, Maria; Kjøløymo, Tina; Nerdal, Anne Marte (Universitetet i Tromsø, 2012)
A major dilemma is that pain free dental treatment using local anaesthesia (LA) is of main importance for avoiding dental fear and anxiety (DFA) at the same time as intraoral injections are strongly associated with DFA. Well-educated dentists and dental hygienists, with a variety of techniques and approaches available, are important to give the patient receiving LA a perception of control. The purpose of this study was to see if clinicians in Norway have heard about, and uses, the steps of anaesthesia (SA) or other forms of cognitive behavioural therapy (CBT). Are there any differences between clinics with (university clinics) and clinics without students from the University in Tromsø in external practise? A questionnaire was sent out using Questback.com to dentists and hygienists in selected clinics in Northern Norway.